Histological Study for the Effect of Squalene Supplements on Muscles Rats Treated with Simvastatin - Oribi, Zainab Amori; Hassan, Mayada S.; Jawad, Mohammed Jasim; Hassan, Mahdi S.; Mohammed, Omar Adel; Alzaidi, Omar H. (Journal of Kerbala for Agricultural Sciences, 2023)
The present study aimed to reveal the biological vitality of squalene supplements and in combination with statins. Statins are a class of drugs that are regularly administered to decrease cholesterol. The main cause of statin discontinuation is the development of statin-associated muscle symptoms. Because of the statin-related myotoxicity phenotypes that are getting worse have been proposed, the study was conducted to examine the effects of squalene supplements in combination with statin. In the experiment, thirty male rats were divided into two group, (experimental one) five rats dosage with normal saline only and other rats administrated with cholesterol 1%/BW for 28 days. Then the second group was randomly divided into four groups (experimental two). The experiment lasted about during two months, the rats were administration as the following groups, first group: six rats used as a negative control group dosage with normal saline only; second group: six rats used as a positive control group dosage with normal cholesterol 1% only; third group: six rats administrated with cholesterol 1%/BW for 28 days then treated with simvastatin 40 mg/kg dosage orally every day for 4 weeks; forth group: six rats administrated with cholesterol 1%/BW for 28 days then treated with squalene 0.2 mg orally every day for 28 day, and fifth group: six rats will have administrated with cholesterol 1%/BW for 28 days then treated with simvastatin 40 mg/kg dosage orally with squalene every day for 28 day. In conclusion: we found from the study effect of squalene supplements on rats treated with statin to avoid side effect and protecting the muscles from damage caused by statin.